The Effect of e-Trust and e-Service Quality on Customer Loyalty on Lazada e-Commoerce in Central Jakarta - Faris, Muhammad; Manap, Abdul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The phenomenon of rapid internet usage in Indonesia opens opportunities for e-commerce platforms, but also presents challenges in maintaining customer loyalty. This study uses a quantitative approach with a survey method through an online questionnaire distributed to 90 respondents who are Lazada users in Central Jakarta. The independent variables in this study are e-trust (X₁) and e-service quality (X₂), while the dependent variable is customer loyalty (Y). The results of the analysis show that both e-trust and e-service quality have a positive effect on customer loyalty. The partial t-test shows that the e-trust variable has a significant effect with a significance value <0.05, as does the e-service quality variable which is also significant on customer loyalty. The simultaneous F-test proves the joint influence of e-trust and e-service quality on customer loyalty. The coefficient of determination (R²) value shows that the e-trust and e-service quality variables are able to explain variations in customer loyalty by 72.4%, while the rest is explained by other factors outside this research model. These findings indicate that increasing customer trust, especially related to transaction security and service reliability, as well as the quality of electronic services such as response speed and system availability, is very important to increase Lazada customer loyalty in Central Jakarta. This research contributes both practically to e-commerce management in formulating customer retention strategies, as well as academically as a reference for further research in the field of e-commerce and consumer behavior.